Conservative therapeutic approach to corrosive poisonings in adults - A. Chibishev; Z. Pereska; N. Simonovska; V. Chibisheva; M. Glasnovic; L. T. Chitkushev (New York : Springer, 2013)
In this study, we assess the effectiveness of a conservative therapeutic treatment of acute corrosive poisonings in adults, and we define therapeutic protocols based on clinical and endoscopic criteria.
Keywords: caustic ingestion; esophagogastroduodenoscopy; acids; alkalis